Kenyamanan Termal pada Bangunan Berventilasi Alami di Iklim Tropis - Iqbal, Muhammad; Atthaillah, Atthaillah; Safyan, Adi; Indriani, Lena; Sina, Aura Mutiara (Nature : National Academic Journal of Architecture, 2024)
Energy consumption in buildings plays a crucial role in determining efficiency and environmental impact. Natural ventilation offers a solution to reduce energy consumption by utilizing outdoor airflow to enhance thermal comfort without significant energy use. This study examines the effects of weather conditions, including temperature, humidity, and wind speed, on the thermal comfort of occupants in naturally ventilated buildings with single-sided openings. Data were collected through measurements of indoor and outdoor weather conditions over 21 days and a perception survey involving 138 respondents, using randomly selected questionnaires. The results indicate that indoor temperature is highly influenced by incoming wind flow, with a strong correlation between outdoor relative humidity and indoor temperature (R = 0.90). A majority of respondents (90.58%) expressed a preference for cooler indoor conditions, indicating discomfort within the building. The study also found consistency in user thermal comfort preferences based on the Thermal Sensation Vote (TSV) and Thermal Comfort Vote (TCV) scales. Recommendations include further investigations into variations in window size, window orientation, and the impact of solar radiation to improve indoor temperature and humidity control, enhancing thermal comfort for building occupants.